Cost-benefit analysis in a climate of change: setting social discount rates in the case of Ireland - O'Mahony Tadhg (AIMS Press, 2022)
The global practice of Cost-Benefit Analysis (CBA), to analyse the welfare impacts of public investments, has undergone profound changes in recent years. The reforms in general practice have primarily been driven by the discussions of the implications of climate change and environmental degradation. Central to the discussion has been the social discount rate, used to value future costs and benefits in the present, and also the dual discount rates for "environmental goods", as goods that are of no, or of risky substitution. Official rates, in many nations, are calculated using the "Ramsey" formula. The literature has explored the relevant factors in this formula, but with less attention paid to the selection of the rate of future growth in consumption, or to the setting of dual discount rates in national practice guidance. Through considering the case of Ireland, this study demonstrates that the selection of growth rates in consumption, in the context of future uncertainty, requires the use of plausible scenarios, rather than historical trends or forecasts. By employing economic scenarios, alongside established values for the other factors, the main discount rate for Ireland is calculated in a range of 1.7 to 2.8 per cent. Seperately, a dual discount rate, for capital that cannot be replaced, is estimated at ≤1.3 per cent. The main discount rate is validated by comparison against discount rates found in the literature, applied in other comparable nations, and by the rate estimated from the real yield on government bonds. All four independent lines of evidence support the range estimated. This demonstrates that the Irish government's estimated discount rate, of 4.0 per cent, is not credible, and needs reduction, alongside introduction of dual discounting.